Petroleum exploration handbook : a practical manual summarizing the application of earth sciences to petroleum exploration - Moody, Graham B. (New York : McGraw-Hill, 1961)
The purpose of this handbook is to summarise and to correlate all the activities involved in petroleum exploration.
Includes bibliographical references.
obn 25/01/2019
Loans
Keywords: Prospecting; Petroleum